Soil fertility and productivity of sugarcane influenced by enriched pressmud compost with chemical fertilizers (SAARC Journal of Agriculture, 2016)
A field experiment was conducted at Bangladesh Sugarcrop Research Institute, Ishurdi, Pabna, Bangladesh to examine the effects of enriched compost with chemical fertilizers on soil fertility and productivity of sugarcane. The experiment was laid out in Randomized Complete Block Design (RCBD) with 16 treatments comprising four levels of inorganic fertilizers (100%, 75%, 50% and 0%) and four levels of pressmud (enriched by Trichoderma harzianum @ 7.5 t ha-1, T. viride @ 7.5 t ha-1, untreated raw pressmud @ 10 t ha-1 and control). It was observed that germination (90.34%), total chlorophyll content (2.58 mg g-1), leaf area index (5.00), dry matter (3.41 kg m-2), tiller (137.94 × 000 ha-1), millable cane stalk (99.15 × 000 ha-1) and yield (111.32 t ha-1) were found maximum in 100% recommended fertilizer (N150 P50 K90 S35 and Zn4 kg ha-1) with enriched pressmud which was statistically identical in comparison with 75% and 50% of recommended chemical fertilizers with enriched pressmud. The N (1.47%), K (1.24%) and S (0.17%) contents of leaf tissues were slightly increased with chemical fertilizers + enriched pressmud compared to chemical fertilizer alone. Soil Organic C, total N, P, K and S were higher with pressmud application compared to non pressmud application. Microbial enrichment of pressmud with Trichoderma sp. could save 2.5 t ha-1 of pressmud and 25% of recommended fertilizers. It can be concluded that enriched pressmud is more effective than raw pressmud in increasing sugarcane yield and maintain soil fertility in High Ganges River Floodplain soils.SAARC J. Agri., 13(2): 183-197 (2015)